Pendampingan Pemberdayaan Masyarakat dalam Meningkatkan Perekonomian Desa: Community Empowerment Assistance in Improving the Village Economy - Harini, Noor; Suhariyanto, Didik; Indriyani, Indriyani; Novaria, Novi; Santoso, Aprih; Yuniarti, Elsa (Amalee: Indonesian Journal of Community Research and Engagement, 2023)
Community empowerment assistance is an important strategy in developing a sustainable and inclusive village economy, where village communities can obtain greater economic benefits and improve their quality of life. This assistance aims to help rural communities develop their area's economic potential to increase the community's income and welfare. The method used in this community service is Community Based Research (CBR) using the Forum Group Discussion (FGD) approach in training and mentoring. The result of this service is that community empowerment assistance can be an effective strategy for improving the village economy. Assistance can be obtained by applying various relevant theories, such as community empowerment, local economic development, social entrepreneurship, and sustainable development. In practice, community empowerment assistance must be carried out in a participatory manner by involving village communities in planning and developing businesses that benefit them.